Application of Particle Swarm Optimization Method in Fleet Transportation Systems of Two-Wheeled Automotive Industry - Sumardiyanto, Hery; Rahmat Rahmat; Dean Anggara Putra; Rifo Nur Laksana; Jefri Imron; Marhanedra Natawibawa (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
One of the activities in the supply chain system in the motorcycle industry is the process of sending components or spare parts from vendors to motorcycle assembly plants. Delivery of spare parts using the respective vendor's fleet. Along with the increase in market demand, demand for components from vendors has also increased. This has an impact on increasing the number and frequency of fleets entering the factory area; besides that, there is also an increase in transportation costs from Vendors. This study aims to improve efficiency in the number, frequency, and cost of fleet transportation by using the VRP (Vehicle Routing Problem) approach. To get optimal results, the PSO (Particle Swarm Optimization) method was used by utilizing the MATLAB 2020 software. This research involved 40 vendors, logistics partners, and motorcycle assembly factories. The results of this study showed better results, namely, before the research was carried out, the number of fleets was 40 units, and the delivery frequency was 40 times, with a total shipping cost of IDR 2,769,330. Meanwhile, after conducting research using the PSO optimization method, it was obtained that the number of delivery frequency fleets was 8 times with a total shipping cost of IDR 2,679,113.